Does load influence shoulder muscle recruitment patterns during scapular plane abduction?. Issue 9 (September 2016) - Reed, Darren; Cathers, Ian; Halaki, Mark; Ginn, Karen A.
Abstract: Objectives: Load is used to increasingly challenge muscle function and has been shown to increase muscle activity levels with no change in activation patterns during shoulder flexion, extension, adduction and rotation. However, the effect of load during shoulder abduction, a movement commonly used in assessment of shoulder dysfunction and to improve shoulder function, has not been comprehensively examined. Therefore, the purpose of this study was to determine if load influences shoulder muscle activation patterns and levels during scapular plane abduction in normal subjects. Design: Experimental study. Methods: Fourteen volunteers performed shoulder abduction in the scapular plane at 25%, 50% and 75% of maximum load. Eight shoulder muscles were investigated using a combination of indwelling and surface electromyographic recordings: middle deltoid, infraspinatus, subscapularis, supraspinatus, serratus anterior, upper and lower trapezius and rhomboid major. Results: All muscles tested showed increasing average muscle activation levels with increasing load and strong correlations in the activation patterns between loads. Conclusions: Increasing shoulder abduction load not only increases activity in middle deltoid but also in the rotator cuff (infraspinatus, subscapularis, supraspinatus) and axioscapular (serratus anterior, upper and lower trapezius, rhomboid major) muscles. The functional stabilising role of both the rotator cuff and axioscapular muscles is considered an important contribution to the increased activation levels in these muscle groups as they function to counterbalance potential translation forces produced by other muscles during shoulder abduction. The activation patterns of all shoulder muscle groups during abduction can be trained at low load and progressively challenged with increasing load.